Predicting species response to disturbance from size class distributions of adults and saplings in a Jamaican tropical dry forest - Mclaren, K.P.; Mcdonald, M.A.; Hall, J.B.; Heale, J.R.
The diversity of tropical dry forests is poorly described and their regeneration ecology not well understood, however they are under severe threat of conversion and degradation. The Hellshire Hills constitute a dry limestone forest reserve on the south coast of Jamaica that is of high conservation value. In order to describe the structure and composition of this forest and assess the extent to which the population structures of its tree species do characterize their regeneration ecologies, pre-disturbance structure, floristics and seedling populations were compared with post-disturbance species responses in twelve 15 m · 15 m permanent sample plots which were laid out in a blocked design in April 1998, giving a total sample area of 0.27 ha. These plots were subjected to disturbance in April 1999 (cutting)with each of four blocks being assigned with two randomly allocated treatment plots (partially and clear cut)and one control plot (uncut). A total of 1278 trees (+2 cm DBH)and 7863 seedlings and saplings (0-2 mm and 2-20 mm root collar diameter (RCD)respectively), comprising 60 and 52 species, respectively, were sampled in the plots prior to disturbance. The species-area curve for trees reached a maximum at 0.20 ha, and abundance was widely distributed amongst the species (26 had importance values greater than 1
Keywords: FUNCTIONAL GROUPS; REGENERATION; RESILIENCE; SEEDLINGS; SIZE CLASS DISTRIBUTION